1983
DOI: 10.1016/0014-5793(83)80965-x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium uptake during the cell cycle of Saccharomyces cerevisiae

Abstract: Synchronous culture of the budding yeast Saccharomyces cerevisiae was obtained by sucrose density gradient selection with 90-100% of yeast synchronized by using the cells in the bottom. In these adult cells bud emergence is coincident with an increase in calcium uptake at 1OOmin of the culture, followed by a return to basal values which are maintained until the end of the first cell cycle of study. The phenothiazine derivatives, trifluoperazine and chlorpromazine inhibit bud emergence and trifluoperazine also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Thus, a rise of the biomass calcium directly after pitching into fresh broth can be due to the starvation that the cells undergo at the end of propagation or a previous fermentation. An earlier report by Saavedra-Molina et al 12 suggested that yeast cells exhibit an increased calcium uptake when they start to bud, then the uptake returns to basal values, which are maintained until the end of the cell cycle. They concluded that after the starting point of cell division, calcium must reach its minimum level to ensure continuous budding.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, a rise of the biomass calcium directly after pitching into fresh broth can be due to the starvation that the cells undergo at the end of propagation or a previous fermentation. An earlier report by Saavedra-Molina et al 12 suggested that yeast cells exhibit an increased calcium uptake when they start to bud, then the uptake returns to basal values, which are maintained until the end of the cell cycle. They concluded that after the starting point of cell division, calcium must reach its minimum level to ensure continuous budding.…”
Section: Resultsmentioning
confidence: 97%
“…The first is that permeability to the drug as well as Ca2+ permeability was changed in these mutants. The second is that TFP affects the intracellular Ca2+ concentration by inactivating calmodulin or causing nonspecific damage of the membrane, There are two recent reports (Saavedra-Molina et al, 1983;Eilam, 1983) that TFP stimulates Ca2+ uptake activity in intact yeast cells. We observed that TFP also increased the calcium content of yeast cells (unpublished result).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, a pool of Ca2+ ion or Mg2+ ion may be essential for nuclear division. Moreover, in synchronous cultures of S. cerevisiae, Ca2+ uptake was found to increase when the cells started budding and then to return to the basal value, which was maintained until the end of the first cell cycle (26). This observation suggested some unknown but crucial role of Ca2+ in the early stage of the cell cycle.…”
mentioning
confidence: 82%